Endovascular treatment of aortic coarctation using covered balloon-expandable stents—a systematic review and meta-analysis - He, Fei; Cao, Zhongze; Wang, Chen; Premaratne, Shyamal; Starnes, Benjamin W.; Shu, Chang; Zhang, Wayne W. (Frontiers in Cardiovascular Medicine, 2024)
Balloon dilation and subsequent balloon-expandable stent implantation are effective treatments to improve the hemodynamic status in coarctation of the aorta (CoA). However, limited evidence exists regarding the safety and efficacy of covered balloon-expandable stents (CBS) in a large cohort.In this meta-analysis, we aimed to evaluate the overall success rate, hemodynamic and anatomical benefits, complications, and mid-term results of CBS for CoA.PubMed, Embase and Cochrane Library databases were systemically researched for studies reporting outcomes of CBS for CoA. Single group rate meta-analyses were performed to calculate estimated pooled procedural success, incidence of complications and re-coarctation. Meta-analysis on standardized mean differences was conducted to compare pre-and postoperative transcoarctation pressure gradients (PG), coarctation diameter, and overall change in systolic blood pressure (SBP). Subgroup analyses were conducted to explore potential sources of heterogeneity.The final analysis included twelve studies with a total of 411 patients. Estimated pooled procedural success was 100% (95% CI: 98%-100%, I 2 =0, P=0.78). Significant decreases in transcoarctation PG and SBP were observed. Pooled incidences of stent-related, aortic and access site complications were 2% (95% CI: 0%-5%, I 2 = 30.4%, P = 0.15), 2% (95% CI: 0%-4%, I 2 = 0%, P = 0.76) and 3% (95% CI: 1%-7%, I 2 = 52.9%, P = 0.02), respectively. Subgroup analyses showed that implantation of BeGraft stent was related to significantly higher incidence of access site complications.Covered balloon-expandable stent implantation for CoA is safe and effective with high rates of procedural success, acceptable incidence of complications, and low incidence of re-coarctation.